Control of water-borne diseases: an Islamic approach - Md Isa, Muhammad Lokman; Jainul, Mohammed Abdullah; Mat Yusof, Afzan (2016)
Scarcity of fresh water is currently blighting the population of least developed countries around the world. According to WHO, waterborne diseases, basically derived from get in touch with contaminatd water are estimated 4.1% of total DALYs (Disability Adjusted Life Years) global burden of disease that leads to death of 1.8 million people every year. Numerous pathogens and chemicals may be potential source of water contamination that leads to waterborne diseases in human beings. A number of pathogens are inactive beyond a host thus cause diseases while in contact with a host. The aim of this article is to identify the cause of water-borne diseases and to find out the approaches to control it in Islamic way. There are quite a lot of Hadiths of Prophet (peace e upon him) regarding the method of cleanliness where numerous Hadiths have scientific background to control waterborne diseases. Causes of water pollution may be natural or men made, intentional or accidental; and people mostly get infected fortuitously either by consuming or getting touched to contaminated water. Scientifically, individual hygiene and sanitation is the most prominent way to prevent waterborne diseases. In Islam, Prophet Muhammad (peace be upon him) puts a great emphasize on purification in terms of personal cleanliness and made it mandatory to follow rule to remain pure both physically and spiritually. Thus it can be said that, Sunnatic approaches of cleanliness possess a great deal to manage waterborne illness.